2013
DOI: 10.1136/jnnp-2013-305514
|View full text |Cite
|
Sign up to set email alerts
|

Stereo-EEG-guided radio-frequency thermocoagulations of epileptogenic grey-matter nodular heterotopy

Abstract: SEEG-guided RF-THC proved to be a safe and effective option in our small case-series of NH-related focal epilepsy. The indications to this treatment were strictly dependent on findings of intracerebral recording by SEEG, which can define the role of the NH in the generation of the ictal discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 23 publications
0
65
1
4
Order By: Relevance
“…9,11,21 With time, as excellent results on seizures became evident in our experience, we were encouraged to offer RF-TC as the first option to patients with this etiology. Therefore, the strategy for electrode arrangement was implemented progressively for extensive coverage of the heterotopy to destroy the lesion as completely as possible, which enabled us to achieve good results not only in the less recent patients with a single nodule 6 but also in those with bilateral (2 patients) or larger heterotopies. In particular, previous studies indicated that patients with bilateral heterotopies are not good candidates for surgical resection.…”
Section: Seizure Outcome After Rf-tcmentioning
confidence: 99%
See 2 more Smart Citations
“…9,11,21 With time, as excellent results on seizures became evident in our experience, we were encouraged to offer RF-TC as the first option to patients with this etiology. Therefore, the strategy for electrode arrangement was implemented progressively for extensive coverage of the heterotopy to destroy the lesion as completely as possible, which enabled us to achieve good results not only in the less recent patients with a single nodule 6 but also in those with bilateral (2 patients) or larger heterotopies. In particular, previous studies indicated that patients with bilateral heterotopies are not good candidates for surgical resection.…”
Section: Seizure Outcome After Rf-tcmentioning
confidence: 99%
“…As a matter of fact, as our experience with SEEG-guided RF-TC increased, it became clear to us that patients with nodular heterotopies are optimal candidates for this treatment option, so the preliminary results on the excellent outcome obtained for 5 of these patients were recently published. 6 Therefore, because the decision to accept RF-TC was made by the patients or their guardians after a thorough discussion with the epileptologists and the neurosurgeons of the team, it is likely that we had a more optimistic attitude when we offered this treatment to patients with nodular heterotopies than to patients with other etiologies. Similar reasons probably explain the considerable rate (24.7%) of patients excluded from surgery after SEEG evaluation in this series, which is higher than that recorded in our whole population of patients who underwent SEEG (approximately 10% 5 ).…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Traditional surgery consisting of the removal of the EZ, not necessarily involving the PNHs, has not frequently had a good outcome, 14,16 whereas other studies have shown poor outcome after a simple temporal lobe resection not inclusive of the nodular malformation. [17][18][19][20][21] The target of this retrospective study was to evaluate the capability of SEEG investigations in defining the site and extension of the EZ in these complex cortical malformations, and the efficacy of SEEG-guided RF-TC in a consecutive series of patients with PNHs, with different clinical and neuroradiologic pictures. Few reports have shown encouraging results coming from the use of these techniques in patients with PNHs, although due to a large heterogeneity and to the very small number of described patients (case reports), it is still difficult to draw conclusions.…”
mentioning
confidence: 99%
“…Cossu and colleagues present their outcome of stereotactic radiofrequency lesioning in nodular heterotopia and show a remarkable rate of Engel class I outcome 1. This adds to the growing volume of publications using stereotactic invasive lesioning combined with high-resolution MRI and invasive stereotactic EEG (SEEG) recordings allowing for a three-dimensional physiological characterisation of the epileptogenic focus techniques used.…”
mentioning
confidence: 94%